The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.7863/jum.2012.31.12.2017
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of Isolated Right Pulmonary Agenesis Using Sonography Alone

Abstract: Pulmonary agenesis is a rare congenital anomaly, estimated to complicate around 1 per 15,000 pregnancies, in which there is complete absence or severe hypoplasia of one or both lungs, frequently associated with other abnormalities. A prospective prenatal diagnosis is a challenge, and a substantial proportion of cases are diagnosed by fetal magnetic resonance imaging, postnatal computed tomography, or postmortem. Thus, there are only a few reported cases of prenatal diagnosis in the literature. We report the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…In recent years, progress achieved in obstetrical imaging has made early antenatal diagnosis possible with largest case series of 18 cases reported by Zhang et al 17 Cases have also been diagnosed antenatally as early as first, 18 second, [19][20][21] and third 22 trimester of pregnancy. In our study, cases 1 and 2 were diagnosed at the second and third trimester, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, progress achieved in obstetrical imaging has made early antenatal diagnosis possible with largest case series of 18 cases reported by Zhang et al 17 Cases have also been diagnosed antenatally as early as first, 18 second, [19][20][21] and third 22 trimester of pregnancy. In our study, cases 1 and 2 were diagnosed at the second and third trimester, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the review by Maltz and Nadas (1968), cardiac and vascular defects were noted in 23% of the 156 reported patients [17]. A more recent review [18] by Meller et al (2012) suggested that left lung agenesis was more frequently isolated than right lung agenesis. They found that only 1 in 6 cases of left lung agenesis had a cardiovascular anomaly, whereas 19 of 25 cases with right-sided presented with a cardiovascular anomaly, the most common of which was scimitar syndrome (15 cases).…”
Section: Discussionmentioning
confidence: 99%
“…44,4850 It is important to note that cardiovascular abnormalities are more frequent in right pulmonary agenesis than in left pulmonary agenesis (76% and 17% respectively). 46 Pulmonary agenesis is not associated with an increased incidence of the chromosomal abnormalities. 44,47 The prognostic in right pulmonary agenesis is poorer than in left pulmonary agenesis; this is explained by the important shift of the mediastinum and by a higher frequency of associated pathologies in right pulmonary agenesis.…”
Section: Dsjuogmentioning
confidence: 94%
“…47,48 The mediastinal shift will bring the problem of a differential diagnosis with the more frequent pathologies, congenital diaphragmatic hernia, CCAM, BPS, or less common malformations, such as pulmonary emphy sema, mediastinal teratoma, neuroblastoma, hetero taxy syndrome. 46 …”
Section: Right Pulmonary Agenesismentioning
confidence: 97%
See 1 more Smart Citation